Portal vein thrombosis following umbilical vein catheterization in neonates - Dr Chandrashekhar C; Dr. Sushma Krishnegowda; Dr. Vikas. VM; Dr. Bhaktavatsala. H.R c (Pediatric Review: International Journal of Pediatric Research, 2015)
Objective: To study the association of portal vein thrombosis in umbilical vein catheterized neonates.Study design: Prospective study.Subjects: Neonates in NICU with umbilical vein catheterization.Methods: Doppler ultrasound was performed for all neonates within 24-48 hours of catheter insertion, followed by 48-72 hours after its removal and weekly until hospital discharge or clot resolution. Diagnosis of Portal vein thrombosis was made, its extent, location and size was noted.Result: 30 newborns were screened for portal vein thrombosis. Among them, 17 (57.2%) babies had clinical sepsis, 14(46.7%) had blood transfusion and 7 (23.3%) had calcium infusion through the umbilical vein. Portal vein thrombosis was observed in 3 out of 30 babies (10%). 2 babies had the umbilical tip in inferior vena cava and one baby had in main portal vein. Color Doppler revealed, two babies had partial non-occlusive thrombus in the left portal vein and one baby had in the main portal vein. On follow up, the thrombus of all the babies had resolved by 1-2 weeks. All the 3(100%) neonates with thrombosis received calcium infusion through the umbilical vein and its association was found to be statistically significant with a P Value of 0.086.Conclusions: Calcium transfusion through umbilical vein catheterization is associated with term portal vein thrombosis, though most of them are clinically silent and resolve spontaneously. Ultrasound can be used as effective tool in early detection of the thrombus and hence as a guide for catheter removal.